Meta-analysis of the risk of mortality with salmeterol and the effect of concomitant inhaled corticosteroid therapy. Issue 1 (22nd December 2009) - Weatherall, M; Wijesinghe, M; Perrin, K; Harwood, M; Beasley, R
Abstract : Background: There is concern that long-acting β agonist (LABA) drugs may increase the risk of asthma mortality. Methods: A meta-analysis was conducted of asthma deaths in randomised controlled clinical trials from the GlaxoSmithKline database that compared salmeterol with a non-LABA comparator treatment in asthma. The Peto one-step method was used to determine the risk overall (all studies) and in derived datasets based on inhaled corticosteroid (ICS) use. Results: There were 35 asthma deaths in 215 studies with 106 575 subjects. Two studies (SMART and SNS) contributed 30/35 (86%) asthma deaths, the overall findings largely reflecting the characteristics of these studies. The odds ratio for risk of asthma mortality with salmeterol was 2.7 (95% CI 1.4 to 5.3). In 54 placebo controlled studies the risk of death from asthma in patients not prescribed ICS was 7.3 (95% CI 1.8 to 29.4). In 127 studies in which patients were prescribed ICS, the risk of asthma death was 2.1 (95% CI 0.6 to 7.9). In 63 studies in which patients were randomised to receive the combination salmeterol/fluticasone propionate inhaler or ICS, there were no asthma deaths among 22 600 patients. Conclusions: Salmeterol monotherapy in asthma increases the risk of asthma mortality and this risk is reduced with concomitant ICS therapy. There is no evidence that combination salmeterol/fluticasone propionate therapy is associated with an increased risk of asthma mortality, although this interpretation is limited by the low statistical power of available studies.